2010
DOI: 10.1021/bm101080p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Carboxylic Acid Conjugated, Hydrophobically Derivatized, Hyperbranched Polyglycerols as Nanoparticulate Drug Carriers for Cisplatin

Abstract: Hyperbranched polyglycerols (HPGs) with hydrophobic cores and derivatized with methoxy poly(ethylene glycol) were synthesized and further functionalized with carboxylate groups to bind and deliver cisplatin. Low and high levels of carboxylate were conjugated to HPGs (HPG-C(8/10)-MePEG(6.5)-COOH(113) and HPG-C(8/10)-MePEG(6.5)-COOH(348)) and their structures were confirmed through NMR and FTIR spectroscopy and potentiometric titration. The hydrodynamic diameter of the HPGs ranged from 5-10 nm and the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 44 publications
1
46
0
Order By: Relevance
“…Nanomedicines with high drug-loading content are usually prepared using processes with high drug-loading efficiency. [11][12][13][14] If the space capacity of the carrier material is low, it is difficult to get high drug-loading content, even if the preparation process of nanomedicines shows high drug-loading efficiency. [15][16][17] Taking into account most of the concepts investigated, high drug-loading efficiency may be necessary but not sufficient for a gain in high drug-loading content.…”
Section: Drug Loading Content (Weight [Wt]%)mentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomedicines with high drug-loading content are usually prepared using processes with high drug-loading efficiency. [11][12][13][14] If the space capacity of the carrier material is low, it is difficult to get high drug-loading content, even if the preparation process of nanomedicines shows high drug-loading efficiency. [15][16][17] Taking into account most of the concepts investigated, high drug-loading efficiency may be necessary but not sufficient for a gain in high drug-loading content.…”
Section: Drug Loading Content (Weight [Wt]%)mentioning
confidence: 99%
“…Following this strategy, Ye et al fabricated HBP-cisplatin conjugates based on hyperbranched polyglycerols (HPGs). 13 In this system, HPGs were modified with hydrophobic alkyl (C 8 /C 10 ) chains into the core, derivatized with methoxy PEG (MePEG) onto the surface, and further functionalized with carboxylate groups on MePEG chains to conjugate and release cisplatin. The drug-loading efficiency of cisplatin was …”
Section: Branched Polymer-drug Conjugatesmentioning
confidence: 99%
“…Intravesical Bacillus Calmette-Guerin (BCG) immunotherapy, the current standard therapy for preventing recurrence and progression in newly diagnosed bladder cancer, suffers from several disadvantages such as BCG intolerance and failure (Witjes, 2006). Chemotherapy has been reported to be generally better tolerated than BCG (Gontero et al, 2010), and drugs such as mitomycin C (Di Stasi et al, 2003;Divrik et al, 2006;Kondas et al, 1999), doxorubicin (Huang et al, 2003;Ueda et al, 1994), cisplatin (Huang et al, 2012;Ye et al, 2011) and gemcitabine (Di Lorenzo et al, 2010;Jones et al, 2012;Shelley et al, 2012;Sternberg et al, 2013) have been used. However, intravesical chemotherapy only prevents recurrence in the shortterm and may not achieve the same effect in the long-term or a reduction in risk of disease progression (Malkowicz, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that CS can cause significant deterioration of the urothelium (Kos et al, 2006). Recently, more tolerable mucoadhesive materials have been designed and evaluated for IDD application in bladder cancer chemotherapy (Carvalho et al, 2010;Hadaschik et al, 2008;Mugabe et al, 2009Mugabe et al, , 2011Mugabe et al, , 2012Ye et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The conjugation of chlorambucil (7 wt%) to these HBPs inhibited 50% of MCF-7 growth at a dose of 120 µg/mL. Ye et al 117 reported the synthesis of hyperbranched polyglycerols (HPGs) with hydrophobic cores derivatized with PEG and functionalized with carboxylate groups in order to conjugate and release cisplatin (Fig. 7).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%